Exercise of Dynamic Stability in the Presence of Perturbations Elicit Fast Improvements of Simulated Fall Recovery and Strength in Older Adults: A Randomized Controlled Trial - Bohm, Sebastian; Mandla-Liebsch, Martin; Mersmann, Falk; Arampatzis, Adamantios (Frontiers in Sports and Active Living, 2020)
Age-related impairments of reactive motor responses to postural threats and reduced muscular capacities of the legs are key factors for the higher risk of falling in older people. It has been evidenced that a training of dynamic stability in the presence of perturbations has the potential to improve these deficits. However, the time course of training effects during such interventions is poorly understood. The purpose of this parallel-group study was to investigate the temporal adaptation dynamics of the balance recovery performance and leg strength during a dynamic stability training. Forty-two healthy older adults (65-85 years) were randomly assigned to a training (n=27, analyzed n=18) or control group (n=15, n=14). The training was conducted in a group setting for six weeks (3x/week, 45 minutes). The exercises focused on mechanism of stability control (i.e. modulation of the base of support and segment counter-rotations around the center of mass) during standing, stepping and jumping on unstable surfaces with a high balance intensity. Before, after three and after six weeks, the maximum plantar flexion moment and knee extension moment was assessed. The recovery performance was evaluated by a simulated forward fall (lean-and-release test) and the margin of stability concept. The margin of stability at release decreased significantly after three weeks of training (34%, effect size g=0.79), which indicates fast improvements of balance recovery performance. The margin of stability further decreased after week six (53%, g=1.21), yet the difference between week three and six was not significant. Furthermore, the training led to significant increases of the plantar flexion moment after week three (12%, g=0.72) and six (13%, g=0.75) with no significant difference between weeks. For the knee extension moment, a significant increase was found only after week six (11%, g=1.07). The control group did not show any significant changes. This study provides evidence that a challenging training of dynamic stability in the presence of perturbations can improve balance recovery performance and leg strength of older adults already after few weeks. Therefore, short-term training interventions using this paradigm may be an effective strategy for fall prevention in the elderly population, particularly when intervention time is limited.